The mondegreen effect in L2 speech perception: An investigation of phonological ambiguity and cognitive expectation in the speeches of Indonesian university students - Adi Sutrisno; Misnadin Misnadin (Universitas Ahmad Dahlan, 2026)
This study investigates the Mondegreen effect in second language (L2) listening by examining how phonological ambiguity and cognitive expectation interact to shape auditory misperception among Indonesian university-level EFL learners. While prior research has often treated L2 listening difficulties as either phonological decoding problems or failures of top-down processing, this study offers an integrated account by analyzing misperceptions across multiple linguistic levels. Data were collected from 165 Indonesian undergraduate students through a listening transcription task involving 12 naturally produced English utterances characterized by connected speech, prosodic variation, and phonological reduction. A total of 1,980 responses were analyzed and categorized into word, phrase, clause, and sentence-level misperceptions. The findings show that 39.9% of responses involved misperception, with sentence-level reinterpretations emerging as the most frequent pattern, followed by word-level substitutions and lower rates at clause and phrase levels. The analysis demonstrates that auditory misperception is systematically triggered by reduced and ambiguous speech signals, which obscure segmentation and activate competing lexical candidates. Crucially, listeners do not merely fail to decode input but actively reconstruct meaning, often relying on top-down expectations that override bottom-up acoustic cues. This study contributes to L2 speech perception research by reframing Mondegreens as evidence of dynamic meaning construction rather than perceptual error. It also highlights the interaction between phonological processing and cognitive expectation in real-time listening. Pedagogically, the findings suggest the need for greater emphasis on prosodic training, segmentation awareness, and metacognitive strategies to enhance learners’ perceptual resilience in authentic listening contexts.